Efektivitas Bimbingan Kelompok dengan Teknik Self-Management untuk Meningkatkan Manajemen Waktu Siswa Boarding School - Mita Tiara Kharisma Putri; Sigit Muryono (Jurnal Bimbingan dan Konseling Pandohop, 2026)
Low time management skills among boarding school students may negatively affect discipline, task completion, and academic achievement. This study aimed to examine the effectiveness of group guidance using self-management techniques in improving time management among students at SMP-SMA Saintek UHAMKA Boarding School. This study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The population consisted of 21 students, while the research sample included 8 students selected through purposive sampling based on low time management scores. The research instrument was a time management questionnaire developed based on the dimensions of setting goals and prioritizing, mechanics of time management, and preference for organization. Data were analyzed using a paired sample t-test. The findings showed an increase in students’ average time management scores from 114.00 in the pretest to 123.25 in the posttest. The hypothesis test yielded a significance value of p = 0.027 (p < 0.05), with Cohen’s d effect size of 0.99. These findings indicate that group guidance using self-management techniques was effective in improving students’ time management in the research group.